Pengelolaan Pajak Bumi dan Bangunan Sektor Perkebunan Dalam Kerangka Desentralisasi Fiskal di Sumatera Barat - Putra, Gustinof Hase; Warman, Kurnia; Rosari, Anton (Faculty of Law, Andalas University, 2024)
Land and Building Tax (LBT) in the Plantation sector is a tax on land and buildings that are owned, benefited from, owned, or controlled by an individual or legal entity located in the area stated in the plantation business permit and plantation business use rights. The management is the authority of the Central Government. In the plantation business, every business actor with a particular land area must have a plantation business permit issued by the Regional Government. The results of this LBT collection are handed over entirely to the regional government through profit-sharing funds. The Problems that will be studied are: How is the management of LBT for plantation businesses in West Sumatra; How is the financial relations between the Central Government and the Regional Governments in managing LBT of Plantation businesses in West Sumatera; and How to delegate the management of LBT in the Plantation Sector to the Regional Government in West Sumatera. The author uses empirical juridical research methods and an analytical description in this writing. The research results concluded that the management of LBT for plantation businesses in West Sumatra is managed by The Central government in the LBT Plantation Sector and The Regional Government in the form of LBT for the Rural-Urban Sector. The Financial relationship between the Central Government and Regional Governments in managing LBT for plantation businesses is to transfer funds to the regions through Tax Profit Sharing and Palm Oil Profit Sharing Funds. Management of LBT in the Plantation Sector should be delegated to The Regional Government, and the Regional Government is capable and ready to manage it.